2007
DOI: 10.11606/issn.1679-9836.v86i1p28-38
|View full text |Cite
|
Sign up to set email alerts
|

Autopercepção de saúde: um estudo com idosos de baixa renda de São Paulo

Abstract: * Trabalho premiado no COMU-Prêmio POC-Medicina Preventiva. 1 Aluno do 4º ano do curso de medicina da Faculdade de Medicina da USP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 14 publications
1
13
1
10
Order By: Relevance
“…With regards to angina for which self-rated health was not associated according to the findings of this study, a difference for older adults of low-income population was observed; they see their health as poor in the presence of this condition, based on the resulting limitations and interference in their daily life (26) . The World Health Survey conducted in 2003 in Brazil with subjects 18 years or older found a prevalence self-perception of not good health among women with angina (27) , although not significantly associated.…”
Section: Discussioncontrasting
confidence: 58%
“…With regards to angina for which self-rated health was not associated according to the findings of this study, a difference for older adults of low-income population was observed; they see their health as poor in the presence of this condition, based on the resulting limitations and interference in their daily life (26) . The World Health Survey conducted in 2003 in Brazil with subjects 18 years or older found a prevalence self-perception of not good health among women with angina (27) , although not significantly associated.…”
Section: Discussioncontrasting
confidence: 58%
“…9,11 Different terms have been used in different studies to denominate self-assessments of health, including self-perception of health, 9,13,22 self-reported health condition, 23 self-reported health status 24 and subjective health status. 25 In the present study, most of the elderly participants classified their health as normal in self-assessment.…”
Section: Discussionmentioning
confidence: 99%
“…This method is clearly easy to apply, viable and inexpensive. 9 Studies that use self-assessments of health status reflect objective health conditions in distinct population groups, particularly in terms of quality of life and functional capacity. 10 Selfassessments indicate true health status, based on an integrated view of the individual, including biological, psychological and social dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations